Assessment of Fire Safety Preparedness in Muhammad Abubakar Rimi Market (Sabon Gari) Kano, Nigeria - R. D. Kabara; M. M. Sahabo; A. S. Habibu (Journal of Applied Sciences and Environmental Management, 2023)
The frequent occurrence of fire disaster in industrial and commercial buildings, shopping malls, and markets in Nigeria has become a serious threat to the nation’s fragile economy. This research is aimed to assess the fire safety preparedness among the marketers in Muhammad Abubakar Rimi market (Sabon Gari) Kano. Interview and questionnaire survey ware conducted to collect data about the level of fire safety preparedness among the tenants within Muhammad Abubakar Rimi market (Sabon Gari). A total of 396 copies of a questionnaire were distributed. A purposive sampling was used to select the market, a stratified sampling was used to stratify the marketers based on the flammability nature of the commodity they sell and availability sampling was employed to collect data directly from the respondent. The data was analyzed using statistical package for social science (SPSS) and presented in pie chart, bar chart, percentages and tables. The result from the analysis revealed that: Majority of respondents (78%) are not well prepared against fire disaster in the market and this is due to their lack of knowledge on fire safety, lack of knowledge and training regarding the use of fire extinguisher. In conclusion, level fire safety preparedness among the tenants is very low. The study recommends for integrated fire disaster management system involving all stakeholders for sustainable commercial activities in Muhammad Abubakar Rimi market (Sabon Gari).